A Sociolinguistic Study on Joke In Ghostbusters 2016 - Dewi Syafitri; Maharani Robiatul Islam (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The objectives of the research were to describe the forms and the functions of joke in Ghostbusters 2016 movie. The researcher used descriptive qualitative method in classifying and analyzing the forms and functions of joke. Ghostbusters 2016 movie was chosen as object of the research. The researcher used documentation in collecting the data. Technique for analyzing the data was identification, classification, reduction, description and conclusion. The result of the research: 1) form; 5 words (proper noun, determiner, uncountable noun), 7 phrases (prepositional phrase, noun phrase, verb phrase), and 59 sentences (simple sentence, complex sentence, compound sentence, imperative sentence, exclamatory sentence). 2) function; joke to build sense of togetherness in informal setting that was used in close relationship 10 jokes, joke to amuse others and her or him self in informal setting that was used in close relationship 22 jokes, joke to hostile others with violent behavior and teasing in informal setting that was used in distant relationship 10 jokes. In brief, the most frequent form and function was used in Ghostbusters 2016 movie was simple sentence and using joke to amuse others and her or him self in informal setting that was used in close relationship was the most frequent used in Ghostbusters 2016 movie. Keyword: sociolinguistics, joke, comedy movie, ghostbusters